Enhancing Sensory Attributes and Shelf Stability of Restructured Beef Steaks for Meat Value Addition - Basha M H S, Abrar; T, Sathu; V N, Vasudevan; A, Irshad; V L, Gleeja (Journal of Meat Science, 2026)
Achieving optimal tenderness and marketability of meat derived from aged  animals with suboptimal characteristics is pivotal for enhancing meat value in  the industry. Meat restructuring is a potent approach to attain this goal, primarily  by formulating restructured beef steaks. These steaks are developed through a  blend of type II (round and chuck in 1:1 ratio) and type III quality cuts (brisket,  plate, and flank in a 1:1:2 ratio), acknowledged for their toughness. This study  focused on standardising chunk size and the proportion of type II and type III  quality cuts in restructured beef production, with a primary focus on assessing  the shelf stability of the standardised product stored at deep freezer conditions  for 60 days. The evaluation covers a broad spectrum of physico-chemical  characteristics, TBARS, tyrosine, colour values, microbiological parameters,  and sensory attributes. Our key findings unveil significant improvements in  sensory attributes, increased pH, consistent cooking yield, and subtle variations  in colour values and microbial counts, with the Restructured Beef Steaks  (SRBS) consistently surpassing the control. Proximate composition, texture  analysis, and shear force values further distinguish SRBS from the control.  This research reinforces the feasibility of producing shelf-stable restructured  beef steaks with superior sensory attributes, with a focus on a combination of  50% type II and 50% type III quality cuts. Vacuum tumbling is highlighted for  its role in enhancing texture, tenderness, and cohesiveness, ensuring extended  deep freezer storage without compromising sensory qualities. Additionally,  the integration of microbial transglutaminase and mincing contributes to  enhancement of sensory attributes.
Keywords: Restructured beef steaks; Microbial transglutaminase; Type II quality chunks; Type III quality minced cuts; Shelf-life study